"IMPLEMENTATION OF CRIME PREVENTION THROUGH ENVIRONMENTAL DESIGN IN MELIA RESIDENCE HOUSING, SOUTH TANGERANG" - Reyhan Taufiq Ramadhan; Muhammad Zaky (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Residential areas have begun to implement a security system using a one-gate system and strict patrols. These facilities are supported by guards or security personnel to ensure the safety of the residential area. This research is expected to contribute to the development of studies in the field of criminology, especially related to the application of the Crime Prevention Through Environmental Design (CPTED) approach. The author acknowledges that by using a descriptive qualitative research type, it is possible to find out how crime prevention strategies and the implementation of CPTED are implemented as an effort to prevent crime in the Residential Areas. Qualitative research itself also allows researchers to conduct direct interviews with sources who will help in collecting data on the issues being researched. This research is related to Ronald V Clarke's Situational Crime Prevention (SCP) Theory, where Situational Crime Prevention and CPTED can complement each other to prevent crime in Residential Area. This theory aims to explain the application of CPTED as a Crime Prevention Strategy so that criminal acts become more difficult to commit. The results of this study can be used as evaluation material and consideration in designing housing environment infrastructure to be safer through CPTED principles.